Status of Ocular Health and Visual Function among Tailors in Siddharthanagar Municipality, Rupandehi- A Cross-Sectional Study - Nau, Bishnu Prasad; Pokhrel, Basant Mani; Bhusal, Bigyan; Yadav, Chandrajeet Kumar; Gurmaita, Raman Kumar (Med Phoenix, 2024)
Introduction: Visual impairment from age related eye conditions is significant global and national health challenges, with high prevalence therefore likely to have a negative impact on their ability to perform optimally which affects their productivity. Hence the main objective of the study is to assess the ocular health and visual functions among tailors in Siddharthanagar municipality. Materials and Methods: In a cross-sectional descriptive study, 197 tailoring community participants were involved in the research of Siddharthanagar municipality from 27th Kartik to 30th Kartik, 2079. A structured questionnaire was used to collect data on Ocular Health and Visual Function among Tailors. Results: Total of 197 participants were involved in the research among them 61.4% were male and 38.6% were female. Immature cataract (14.97%) followed by meibomitis (9.0%) were the most prevalent form of ocular disorders. Normal visual acuity was present in 66.0% of participants whereas 17.76% were hypermetropic, and 16.64% were myopic. Color vision was normal in 94.41% whereas 4.06% had a red-green deficiency and 1.52 % were not applicable for the test. Contrast sensitivity was normal in 89.98%, 8.12 % had a significant loss, 0.5% had severe loss of contrast and 1.52% were not applicable for the test. The visual field was normal in 98.48% of participants. Increased level of near point of convergence was noticed in 44.67% and 26.90% had decreased amount of near point of convergence. Accommodative insufficiency was noticed in 9.13% among patients below 40 years of age. Schirmer test revealed 32.48% had dry eyes. Conclusion: Regular time interval examining ocular health and visual function in tailors and notifying them about the importance of proper use of spectacle plays a notable role in the acknowledgement of ocular risk factors and its early elimination, improvement of their work productivity and quality of life.